Trends in Antimicrobial Prescription for Inpatients in Changsha, China, 2003 to 2014 - Yinhua ZHANG; Qun YUAN; Xia YI; Honghua LIU; Xiaoyan PAN; Jingwei LIU; Yi XU; Yang CHEN; Guoping HE (Tehran University of Medical Sciences, 2017)
Background: China had implemented policies to limit antimicrobials prescription since 2004; we conducted this study to reflect the effect of these national policies by analyzing antimicrobial prescription trends of medical insurance in patients from 2003 to 2014 in Changsha city, China. Methods: The participants were inpatients of the medical insurance of urban workers (UEBMI). Data were extracted from medical insurance information system of Changsha Medical Insurance Institution, which directly connects with hospitals information systems. Results: Trend analysis showed great changes in antimicrobial prescription and inpatients' cost on antimicrobials over the study period. Antimicrobial prescription rates gradually declined over the study period from 79.0% in 2003 to 43.5% in 2014 (adjusted OR0.205; 95%CI 0.198 to 0.213). There was a quicker decline from 2011 to 2014 (with implementing national antimicrobial stewardship action plan) than the period from 2003 to 2010 (with implementing antimicrobials use education and self-management strategies). The proportion of inpatients used one antimicrobial increased significantly from 25.6% in 2003 to 46.7% in 2014, while the proportion of inpatients used three or more antimicrobials gradually decreased. Bacterial culture rate increased from 20.4% in 2003 to 36.6% in 2014 (adjusted OR 2.248; 95% CI 2.149 to 2.352). The average costs on antimicrobials decreased significantly, from 277.43 US Dollar in 2003 to 91.05 US Dollar in 2014. Conclusion: National efforts to promote rational use of antimicrobials in clinical practice have had a positive effect over the past decade in China.